The Urgency of Regulation and Governance of Artificial Intelligence (AI) in Indonesian Finance: Comparison and Risk-Based Implementation - Afiq Ahmad Hani; Hasbir Paserangi; Arni Viratami Cahyani (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
The rapid advancement of Artificial Intelligence (AI) presents significant opportunities and considerable challenges for the Indonesian financial sector. This paper examines the urgent need for a comprehensive regulatory framework and adaptive oversight mechanisms to govern AI applications in digital financial services in Indonesia. Currently, existing regulations are fragmented and insufficient to address the complexities of AI, including algorithmic accountability and potential biases that could lead to consumer detriment and systemic risks. This research employs a normative legal method, utilizing statutory, conceptual, and comparative approaches by benchmarking Indonesia's legal landscape against international best practices in the European Union, the United States, and Singapore. The study identifies a critical regulatory gap concerning legal liability for AI-induced losses, currently reliant on general civil code provisions (Article 1367 KUHPerdata) that may not adequately cover the autonomous nature of AI. It argues for the necessity of specific AI regulations focusing on risk-based approaches, transparency, accountability, and robust consumer protection, drawing insights from frameworks like the EU AI Act. The paper concludes by recommending institutional reforms and the strengthening of AI governance, grounded in Pancasila principles, to foster a secure, ethical, and inclusive digital financial ecosystem in Indonesia. This will ensure that AI innovation proceeds responsibly, safeguarding the public interest and national financial stability.